Stimulus payments and private transfers - Thomas F. Crossley; Paul Fisher; Peter Levell; Hamish Low (Institute for Fiscal Studies (IFS), 2022)
Private transfers can affect the spending response to stimulus payments, as those receiving income windfalls may transfer resources to other households in greater financial need. We report a survey experiment where individuals were asked how they would respond to a 500 payment, with a randomly selected subset of individuals explicitly told that all households would receive the same payments (a 'public windfall' scenario). This additional information increased MPCs by 11%. Reported transfer intentions in response to windfalls suggest that public payments crowd out private transfers, partly accounting for the higher MPCs in the public windfall case.
Keywords: D12; D14; E21; 330; spending; transfers; MPCs; survey experiment